The importance of obstructive sleep apnea score and end-tidal CO₂ level in adolescent children who underwent oropharyngeal surgery (Annals of Medical Research, 2023)
Aim: Children with obstructive sleep apnea have an increased postoperative risk of adverse respiratory events. In our study, we calculated Obstructive Sleep Apnea Scores using the modified STOP-Bang questionnaire in children undergoing oropharyngeal surgery. The groups determined according to this score were compared in terms of mask ventilation levels in the intraoperative period, postoperative complications and postoperative ETCO₂ levels.Materials and Methods: A total of 90 patients, aged 7-15 years, who will undergo oropharyngeal surgery, classified as ASA I-II, and who have undergone a modified STOP-Bang questionnaire at the preoperative examination, were included in the study. Obstructive sleep apnea score (OSAs) was determined according to the modified STOP-Bang questionnaire, and the patients were divided into 3 groups as low, medium, and high-risk. Difficult mask ventilation level was noted in the intraoperative period. At the end of the operation, end-tidal carbon dioxide concentration (ETCO₂) values at 0, 3, 5, 10, and 15 minutes after the patient was extubated and whether the patient had spasms were recorded.Results: Among the 8 parameters in the modified STOP-Bang questionnaire, it was found that there was a significant difference between the groups for the other 6 parameters except for snoring and learning disability. Diffucult mask ventilation increased significantly from Group I to Group III. There is a significant difference between Group I and II, Group II and III, and Group I and Group III (p= 0.001). Although there were small differences within the groups and between the measurements of ETCO₂ at different minutes, these differences were not statistically significant (p≥0.05).Conclusion: In conclusion, associations between the results of the modified STOP-Bang questionnaire and the level of intervention required for difficult mask ventilation, this information could serve as a useful indicator for a higher level of care in the perioperative period for future patients.
Keywords: Obstructive sleep apnea syndrome; Modified STOP-Bang questionnaire; Difficult mask ventilation level; End-tidal CO₂; Pediatric oropharyngeal surgery